New and newly recorded micro-caddisfly species (Insecta: Trichoptera: Hydroptilidae) from Australia’s north, including islands of Torres Strait - Wells, Alice; Dostine, Peter (Zootaxa, 2016)
From the north of Australia’s Northern Territory, far northeastern Queensland and Torres Strait Islands, six new species of microcaddisfly are described: Hydroptila roperi sp. nov., Hellyethira khukri sp. nov., Oxyethira (Trichoglene) bamaga sp. nov., Oxyethira (Dampfitrichia) torresiana sp. nov., Orthotrichia pethericki sp. nov., and Orthotrichia becca sp. nov. Oxyethira torresiana is recorded from the northwest of York Peninsula and Badu Island in the Torres Strait as well as from Papua New Guinea. Northern Australian records are given for Orthotrichia veikaba Wells and Orthotrichia ensiformis Wells, previously known only from Papua New Guinea. Northern Australian distributions are extended eastwards for  Tricholeiochiton jabirella Wells and westwards for Oxyethira (Trichoglene) triangulata Wells, until now recorded only from the Northern Territory and northeastern Australia, respectively. Brief notes are given on collecting methods and sites.